APPLICATION OF ARTICLE 27 PARAGRAPH (2) OF THE MARRIAGE LAW ON THE MISCONCEPTION OF THE APPLICANT IN MARRIAGE ANNULMENT - Adrian, Luzavindra Maulana; Umar Haris Sanjaya (Domus Legalis Cogitatio, 2025)
This study aims to analyze the application and interpretation of the norms of Article 27 paragraph (2) of the Marriage Law regarding misconception in a petition for annulment of marriage. The problems examined in this study are how the norms of misconception are applied in the application for annulment of marriage and how misconception is interpreted in the application for annulment of marriage. This writing uses normative juridical legal research methods. The approach method used is the statutory approach and case approach. The sources of legal materials used in this research are primary, secondary, and tertiary legal materials. Data collection uses qualitative data analysis methods. The results of this study indicate that the application of the norm of misconception can be used to annul a marriage and must meet the time period set by law. Misconception can be interpreted as a mistake in assessing the identity of the spouse from what is in fact to what is not in accordance with reality and misjudging the spouse's personal condition from normal to abnormal. This study recommends the need for the parties to find out carefully and thoroughly about themselves, including the identity and condition of the partner by utilizing taaruf as a process of getting to know each other before heading to the level of marriage, and the parties also need to find out information about themselves to other parties such as friends and family of the prospective partner.